دراسة نقدية - طعن الحداثيين في السنة النبوية بالوضع - Klaina, Mekki; Yachaoui, Hanane (Asian Journal of Islamic Studies and Da'wah, 2025)
This study addresses a significant issue concerning the doubts raised by modern Arab writers about the authenticity of the Prophetic Sunnah, particularly their claim that fabricated Hadiths have been mixed with authentic ones. These allegations, presented as original ideas by their proponents, in reality, heavily rely on Orientalist studies. The importance of this study lies in defending the integrity of the Prophetic Sunnah and demonstrating the methodology developed by Hadith scholars for its preservation. The research aims to explore these claims, trace their origins, and provide a scholarly response based on strong foundations. The main challenge is to uncover these misconceptions and clarify that the Sunnah has been meticulously preserved. The study adopts a historical, analytical, and critical approach, examining the claims of fabrication, the foundations they rely on, and the origins of their proponents' ideas, while providing a critique of them. The key findings reveal that these modern criticisms lack robust evidence and are primarily based on Orientalist sources, often marked by intellectual dishonesty. Furthermore, the research demonstrates that Hadith scholars have accurately identified and classified fabricated Hadiths, ensuring the authenticity and preservation of the Prophetic Sunnah.